Inter-Religious Inheritance Relationship - Aseri, Muhsin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The general principle of the Qur'an regarding inheritance rules is that every relative gets an inheritance in a fair and balanced manner, regardless of gender, small or old children, or religious differences. When there is a hadith that explicitly states that religious differences are a barrier to inheriting each other, it has implications for inheritance law problems for relatives of different religions. This study aims to reveal how the inheritance relationship between religions is for heirs. This research, which is literature research, is sourced from primary, secondary, and tertiary legal materials with conceptual and philosophical approaches and using qualitative descriptive analysis. This study found that religious differences remained a barrier to inheritance. However, the obstruction of both parents and relatives from obtaining an inheritance due to religious differences does not prevent them from obtaining a share of the inheritance of the testator through the legal will or wills of obligatory.